2021
DOI: 10.1002/wps.20905
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive transcranial magnetic stimulation for smoking cessation: a pivotal multicenter double‐blind randomized controlled trial

Abstract: Repetitive transcranial magnetic stimulation (rTMS) is a non-invasive brain stimulation method increasingly used to treat psychiatric disorders, primarily depression. Initial studies suggest that rTMS may help to treat addictions, but evaluation in multicenter randomized controlled trials (RCTs) is needed. We conducted a multicenter double-blind RCT in 262 chronic smokers meeting DSM-5 criteria for tobacco use disorder, who had made at least one prior failed attempt to quit, with 68% having made at least three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(111 citation statements)
references
References 40 publications
3
102
0
6
Order By: Relevance
“…Even so, we can also hypothesize that the "downregulated craving and improved control" therapeutic interval induced by rTMS may offer the possibility of breaking the addiction cycle by enabling patients to gain more benefit from standard drug treatment and rehabilitation programs. Further protocols could also evaluate the efficacy of maintaining rTMS sessions after successful response to initial stimulations, as proposed in depression [123] or in a recent multicenter randomized control trial in tobacco use disorder [124]. Long-term positive results of these protocols have also been suggested by an observational study in a large cohort in cocaine use disorder [125].…”
Section: Discussionmentioning
confidence: 99%
“…Even so, we can also hypothesize that the "downregulated craving and improved control" therapeutic interval induced by rTMS may offer the possibility of breaking the addiction cycle by enabling patients to gain more benefit from standard drug treatment and rehabilitation programs. Further protocols could also evaluate the efficacy of maintaining rTMS sessions after successful response to initial stimulations, as proposed in depression [123] or in a recent multicenter randomized control trial in tobacco use disorder [124]. Long-term positive results of these protocols have also been suggested by an observational study in a large cohort in cocaine use disorder [125].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies support the use of rTMS for nicotine dependence in healthy smokers (15)(16)(17)(18)(19)(20)(21). Most of these studies have used high frequency 10 Hz rTMS delivered to the left dorsolateral prefrontal cortex (DLPFC) ranging from a 15-min single-session (17) to multi-session experiments (15,16,19,21).…”
Section: Nibs For Nicotine Dependence Targets the Dorsolateral Prefro...mentioning
confidence: 99%
“…Multiple studies support the use of rTMS for nicotine dependence in healthy smokers (15)(16)(17)(18)(19)(20)(21). Most of these studies have used high frequency 10 Hz rTMS delivered to the left dorsolateral prefrontal cortex (DLPFC) ranging from a 15-min single-session (17) to multi-session experiments (15,16,19,21). High frequency stimulation of the DLPFC has been proposed to activate this region and thereby improve "top-down" regulation of brain regions involved in craving and drug-seeking behavior (22).…”
Section: Nibs For Nicotine Dependence Targets the Dorsolateral Prefro...mentioning
confidence: 99%
“…The insula was hypothesized to be a promising target, due to it being an important region in interoception and integrating internal states and strongly associated with craving [ 71 ]. Furthermore, this stimulation protocol was intended to parallel the protocol that was shown to be effective in smoking cessation [ 72 , 73 ]; however, these smoking trials used an H4 coil, which stimulated not only the insula, but also the bilateral prefrontal (which the H8 coil does not). Lastly, two studies of single-session cTBS to a total of 3600 pulses to the MPFC demonstrated the ability to modify fronto-striatal activity on functional MRI but not on self-reported craving [ 66 , 67 ], and requires further study with a full course of treatment.…”
Section: Evidence For Rtms In Audmentioning
confidence: 99%
“…These protocols aim to exploit mechanisms of task-dependent plasticity, as once a disorder specific neurocircuit is “activated”, it may be more primed for neuromodulation by rTMS. For example, dTMS for the treatment of nicotine addiction is done with the pairing of smoking-related cues during treatment [ 73 ]. This combined method resulted in clinically significant findings within a multi-site RCT, which led to FDA approval.…”
Section: Future Directions To Optimize Efficacy Of Rtms For Mdd and Audmentioning
confidence: 99%